A direct-write, resistless hard mask for rapid nanoscale patterning of diamond - CROSS, GRAHAM; PETHICA, JOHN (My University, 2011)
We introduce a simple, resist-free dry etch mask for producing patterns in diamond, both bulk and thin deposited films. Direct gallium ion beam exposure of the native diamond surface to doses as low as 1016 cm-2 forms a top surface hard mask resistant to both oxygen plasma chemical dry etching and, unexpectedly, argon plasma physical dry etching. Gallium implant hard masks of nominal 50 nm thickness demonstrate oxygen plasma etch resistance to over 450 nm depth, or 9:1 selectivity. The process offers significant advantages over direct ion milling of diamond including increased throughput due to separation of patterning and material removal steps, allowing both nanoscale patterning resolution as well as rapid masking of areas approaching millimetre scales. Retention of diamond properties in nanostructures formed by the technique is demonstrated by fabrication of specially shaped nanoindenter tips that can perform imprint pattern transfer at over 14 GPa pressure into gold and silicon surfaces. This resistless technique can be applied to curved and non-planar surfaces for a variety of potential applications requiring high resolution structuring of diamond coatings.
PUBLISHED
Keywords: Condensed matter physics; thin films; diamond; Nanoscience & Materials